2019
DOI: 10.1590/2447-536x.v25i4.2049
|View full text |Cite
|
Sign up to set email alerts
|

Vigor of zinnia seedlings produced in alternative substrate in trays with different cell size

Abstract: The zinnia (Zinnia elegans Jacq.) is an ornamental plant used in landscape composition and presents great potential for cultivation as a cut flower, potted. Faced with the new trend of integrated flower production, that proposes more environmentally friendly practices aiming at sustainability, there is a need to determine alternative substrates that allow the production of quality seedlings. Therefore, this study aimed to evaluate the vigor and quality of zinnia seedlings produced in alternative substrates in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
1
9
0
1
Order By: Relevance
“…Lower dry weight of roots and total per seedling were obtained in the tray with 200 cells only for older seedlings, 46 and 53 days old, while for younger seedlings (39 days) there was no difference between the trays (Table 2). Seedlings produced in trays with lower volume cells restrict seedling growth due to less substrate and space for root growth (Seabra Júnior et al, 2004;Pêgo et al, 2019), even if the number of roots is not restricted (Table 1), as observed in this work. Cells with less volume may restrict the availability of nutrients, oxygenation, water and other essential elements for seedling growth (Seabra Júnior et al, 2004).…”
Section: Resultssupporting
confidence: 63%
“…Lower dry weight of roots and total per seedling were obtained in the tray with 200 cells only for older seedlings, 46 and 53 days old, while for younger seedlings (39 days) there was no difference between the trays (Table 2). Seedlings produced in trays with lower volume cells restrict seedling growth due to less substrate and space for root growth (Seabra Júnior et al, 2004;Pêgo et al, 2019), even if the number of roots is not restricted (Table 1), as observed in this work. Cells with less volume may restrict the availability of nutrients, oxygenation, water and other essential elements for seedling growth (Seabra Júnior et al, 2004).…”
Section: Resultssupporting
confidence: 63%
“…For the ornamental species Lantana camara L., the authors Barone et al (2018) also observed that sewage sludge, used pure or in mixtures with pupunha bark (Bactris gasipae Kunth) positively influenced the height growth of seedlings and attributed these findings to the high contents of nutrients and organic matter in the composition of these substrates. Additionally, Pêgo et al (2019) when evaluating the quality of Zinnia elegans seedlings produced in alternative substrates obtained greater seedling height with the substrate obtained by composting agricultural waste and, Barroso et al (2020) when producing seedlings of the same species in substrates based on carnauba bagasse observed an increase in height with the increase in the proportion of compost in the substrates. Thus, it is possible to observe that the presence of organic matter in the substrates has become indispensable for the growth in height of the seedlings, as reported by Cordeiro et al (2020) and who stated that the organic portion is responsible for the supply of nutrients and presents the best results in the production of seedlings.…”
Section: Resultsmentioning
confidence: 90%
“…It tolerates dry and sunny environments, which makes it suitable for places where growing other types of flowers would be difficult (Zamiran et al, 2013;Ahmad et al, 2015;Pallavi et al, 2017). Although it has great potential for use medicine and phytoremediation, in Brazil there are few studies that address the process of seedling production using substrates from organic waste (Sousa et al, 2011;Pêgo et al, 2019;Barroso et al, 2020Gomaa et al, 2020Panda et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…), species of the Asteraceae family of great potential in Brazil that presents an immense diversity of colors and petal shapes (Franzen et al, 2016), there are few studies about the longevity and postharvest characteristics of its flowers. Parameters such as density, porosity and water retention capacity of the growth substrate are known to influence the initial development of zinnia, and its floral quality (Pê go et al, 2019;Sardoei et al, 2014). As regards the influence of irrigation management, Heidari et al (2016) illustrated that growing plants under low water availability in arid or semi-arid climates leads to a decrease in the postharvest durability of zinnia flowers, cv.…”
Section: Introductionmentioning
confidence: 99%